Single-cell transcriptomic analysis of mouse neocortical development - Lipin Loo (Nature Portfolio, 2019)
The authors perform single-cell RNA-seq of the mouse neocortex at an embryonic time point and at birth, and identify new and known cell types, and cell relatedness within and across age. These data serve as a resource to understand brain development and the cellular origins of brain diseases.